Are chaebol firms ethical?. (5th October 2020) - Hong, Soonwook
The present study investigates the ethics of chaebol firms. The ethics includes both external ethics and internal ethics. The ethics of chaebol firms is tested using corporate social responsibility (CSR), which represents corporate external ethics, and earnings management, which represents corporate internal ethics. The empirical result shows that chaebol firms conduct less accrual earnings management, while conducting more real earnings management. Chaebol firms are found to be active in CSR activities. That is, chaebol firms seem to be ethical externally, but unethical internally. In addition, those chaebol firms that diligently conduct CSR activities are shown to conduct less accrual and real earnings management. Although chaebol firms are unethical internally, active CSR activities are judged to reduce the internal unethicality of chaebol firms. The present study is meaningful in that it analyses the ethics of chaebol firms, which occupy a considerable proportion in South Korean economy, from various angles.